Pengaruh Pengetahuan dan Motivasi terhadap Tingkat Partisipasi Masyarakat Jember dalam Pembayaran Zakat Secara Online di Kabupaten Bandung - Lira Parahita Agni Putri (Jurnal Al-Tatwir, 2021)
The advancement of the world of information technology or what is called IT (Information Technology) is currently growing rapidly along with the development of human needs. Reliable information technology will make it easier for humans to get all kinds of information they want and need quickly, easily and efficiently. Web-based Zakat Payment Service is an Internet application that provides information services regarding online Zakat payments and calculations as well as other information related to Zakat by utilizing Internet technology. This research is a quantitative observational study with a cross sectional approach. So in this study will discuss whether there is a significant influence on the knowledge variable on the participation of the Jember community in paying zakat online. And whether there is a significant effect on the motivation variable on the participation of the people of Bandung Regency in paying zakat online. And whether there is a significant influence between the variables of knowledge, motivation on public participation in paying zakat online in Bandung Regency. The conclusions from the results of this study can be stated as follows: 1) The test results show that Knowledge has a significant and positive effect on Community Participation 2) The test results show that Motivation has a significant and positive effect on Community Participation. 3) The test results show that knowledge and motivation together have a positive effect on online zakat participation in the people of Bandung Regency.